Aortic and mitral bioprosthetic valve dysfunction: surgical or percutaneous solutions?. (8th October 2021) - Belluschi, Igor; Buzzatti, Nicola; Castiglioni, Alessandro; De Bonis, Michele; Maisano, Francesco; Alfieri, Ottavio
Abstract: In the last years, there has been a trend to prefer biological prostheses, especially among young patients, with the aim to avoid anticoagulant treatment. Surgical tissue valves have so far demonstrated their solid long-term durability. However, younger age has been identified as one of the main risk factors for developing structural valve deterioration (SVD). As a consequence, the proportion of subjects at risk for valve dysfunction will constantly rise in the near future. However, while surgical reintervention has always been considered the gold standard for treatment of prosthesis deterioration, the introduction of transcatheter heart valves could offer new therapeutical options, particularly among high-risk patients, aiming a second less invasive chance. The recent standardization of valve durability definitions will soon allow a more comprehensive understanding of the mechanism underlying SVD and guide the choice of prosthesis for patients needing valve replacement.